Azlocillin compared with carbenicillin in the treatment of bronchopulmonary infection due to Pseudomonas aeruginosa in cystic fibrosis. Issue 4 (April 1984) - Penketh, A; Hodson, M E; Gaya, H; Batten, J C
Abstract : A randomised controlled open comparison of azlocillin and gentamicin versus carbenicillin and gentamicin was carried out in patients with cystic fibrosis who were chronically infected with Pseudomonas aeruginosa. The clinical response was assessed by measurements of pulmonary function and of the patients' feelings of wellbeing scored on a visual analogue scale. The sputum penetration of the antibiotics used was also studied. The two groups of 10 patients were similar in terms of age, sex, and pulmonary function at entry to the trial. Both regimens produced significant improvement in pulmonary function over 10 days. The mean FEV1 in the azlocillin group increased from 1206 to 1760 ml (p less than 0.001). In the carbenicillin group the mean FEV1 increased from 1116 to 1619 ml (p less than 0.001). Significant improvements in peak expiratory flow rate, forced vital capacity, and score on the visual analogue scale were also seen but there was no significant difference between the antibiotic regimens. Despite high serum concentrations the sputum penetration of the antibiotics was poor.